2014
DOI: 10.3349/ymj.2014.55.5.1430
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Postoperative Nausea and Vomiting in Patients with Fentanyl-Based Intravenous Patient-Controlled Analgesia and Single Antiemetic Prophylaxis

Abstract: PurposeWe evaluated the incidence and risk factors of postoperative nausea and vomiting (PONV) in patients with fentanyl-based intravenous patient-controlled analgesia (IV-PCA) and single antiemetic prophylaxis of 5-hydroxytryptamine type 3 (5 HT3)-receptor antagonist after the general anesthesia.Materials and MethodsIn this retrospective study, incidence and risk factors for PONV were evaluated with fentanyl IV-PCA during postoperative 48 hours after various surgeries.ResultsFour hundred-forty patients (23%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
3
37
2
1
Order By: Relevance
“…Of the remaining 18 studies, seven were excluded because they were review articles and two were excluded because they were designed for chemotherapy-induced nausea and vomiting (Kappa = 0.896). The full texts of the remaining nine studies were reviewed in more detail; two more studies were excluded because one did not include palonosetron or ramosetron [12] and one was an abstract, not a published article [13]. An additional study, found through a Google search, met the inclusion criteria and was included in this meta-analysis [14].…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 18 studies, seven were excluded because they were review articles and two were excluded because they were designed for chemotherapy-induced nausea and vomiting (Kappa = 0.896). The full texts of the remaining nine studies were reviewed in more detail; two more studies were excluded because one did not include palonosetron or ramosetron [12] and one was an abstract, not a published article [13]. An additional study, found through a Google search, met the inclusion criteria and was included in this meta-analysis [14].…”
Section: Resultsmentioning
confidence: 99%
“…High level epidural analgesia and intravenous opioid analgesia are two common methods used for upper abdominal pain [5]. However, high level epidural block analgesia is technically challenging ,and application of opioids may result in many adverse reactions, such as excessive sedation, respiratory depression, and deceleration of gastrointestinal motility [6][7][8], which are not conducive to rapid recovery. Those disadvantages lead a search for other analgesic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this study finding is high when compared with the studies in developed countries. A recent study in South Korea by J.Choi found the incidence of PONV was 23% (30). Similarly, in Turkey it was found to be 25% (31).…”
Section: Discussionmentioning
confidence: 94%